Determinasi Bakteri Simbion Luminesensi Cumi Loligo edulis Serta Analisis Potensinya Sebagai Anti Bakteri - Delianis Pringgenies; Dinny Anjang Sari; Ria Azizah T.N.; Ervia Yudiati; Endang Sri Susilo; Alfi Satriadi (Universitas Diponegoro, 2017)
The aim of this research is to determine luminous bacteria that symbiont with the light organ of the squid Loligo edulis and also to find out the potency of simbiont bacteria in light organ of the squid L. edulis. The squid L. edulis were collected from Teluk Awur Waters, Jepara. Stages of this research began with the isolation of bacteria, bacteria screening for anti bacteria, antibacterial activity test and and determination of bacterial species of the isolate. The result of determination showed that luminous bacteria which symbiont with the light organ of the squid L. edulis is come from species of Photobacterium phosphoreum. The result showed that luminous bacteria which symbiont with the light organ of the squid L. edulis have potency as antibacterial compound. Bacteria P. phosphoreum which symbiont in light organ of the squid L. edulis could inhibit the growth of Vibrio harveyi (diameter of resistance zone had range from 8,30-8,87 mm), Escherichia coli (diameter of resistance zone had range from 7,84-8,45 mm), Staphylococcus aureus (diameter of resistance zone had range from 8,39-9,09 mm) and Bacillus sp (diameter of resistance zone had range from 8,27-9,01). Tujuan dari penelitian ini adalah untuk mendeterminasi bakteri simbion yang bercahaya yang pada organ ringan dan mengetahui potensi bakteri simbion pada organ ringan dari cumi cumi Loligo edulis. Cumi L. edulis dikoleksi dari perairan Teluk Awur, Jepara. Tahapan penelitian meliputi: isolasi bakteri, skrining bakteri, uji aktivitas antibakteri dan dan identifikasi spesies bakteri isolat. Hasil penelitian memperlihatkan bahwa bakteri luminensensi yang bersimbiosis dengan organ cahaya cumi L. edulis adalah bakteri jenis Photobacterium phosphoreum. Bakteri luminesensi yang menempel pada organ cahaya cumi L. edulis memiliki potensi sebagai senyawa antibakteri. Bakteri P. phosphoreum yang tergabung edulis dapat menghambat pertumbuhan bakteri pathogen Vibrio harveyi (diameter zona resistansi berkisar antara 8,30-8,87 mm), Escherichia coli (diameter zona resistansi berkisar antara 7,84-8,45 mm), Staphylococcus aureus (diameter zona resistansi berkisar antara 8,39-9,09 mm) dan Bacillus sp (diameter zona resistansi berkisar antara 8,27-9,01).